Giving kids a boost: The positive relationship between frequency of SNAP participation and Infant's preventative health care utilization. (September 2021) - Arteaga, Irma; Hodges, Leslie; Heflin, Colleen
Abstract: Well-child visits are protective for child health but underutilized in the United States. The Supplemental Nutrition Assistance Program (SNAP), the largest federal food assistance program in the United States, has been shown to reduce food insecurity and may also promote child health by supporting preventative health care utilization. We examined the relationship between SNAP participation and infant well-child visits using state administrative data from Missouri's Department of Social Services for the period January 2006 to July 2014 for more than 50, 000 infant-mother dyads. We find that compared to always receiving SNAP, leaving SNAP or receiving SNAP unstably reduces the likelihood that an infant receives all recommended well-child visits in the first year. These patterns are more pronounced for infants living in urban areas, infants with Black or Hispanic mothers, and infants whose mothers are diagnosed with depression. We also find that stable SNAP participation primarily influences vaccination rates through well-child visits, which is when most infants receive their immunizations. Given the increased public health risk of foregone care, these results may inform policy makers as they consider making permanent policy waivers to reduce the administrative burden of the recertification process and increase the stability of SNAP participation. Highlights: Leaving SNAP reduces the likelihood an infant receives all recommended well-visits. Receiving SNAP unstably reduces the likelihood of infants receiving five well-visits. These patterns are larger for Hispanics, Blacks, and infants living in urban areas. The "leaving SNAP" pattern is larger for infants with mothers with depression. Stable SNAP participation mainly influences vaccinations through well-child visits.